Regards Sur L’analyse Criminelle - Gakoue, Sokrou Adélaïde (European Scientific Journal, ESJ, 2017)
Criminal analysis, which is a complementary tool for carrying out investigation, reflects a modern conception of criminal investigation. During these investigations, two main categories of analysis were combined: strategic and operational. They are linked to the offense, to the author, and to the method of crime control. Criminal analysis is also a valuable method that optimizes the results of the judicial inquiry through the use of state-of-the-art technology. To achieve their objectives, and for the sake of efficiency, experts in criminal analysis combines their techniques with those of criminal profiling. However, difficulties in the production of certain graphical representations exists, giving rise to the need to consolidate the methods practiced.